On the biology of Acanthephyra pelagica (Decapoda: Natantia: Oplophoridae) of the North Atlantic subtropical convergence zone - Rudolf N. Burukovsky; Victoria M. Andreeva (Журнал Сибирского федерального университета: Серия Биология, 2010)
In the region of northwards and eastwards from the Azores between latitudes 46-37°N and longitudes 14-29°W Acanthephyra pelagica biology was investigated during the summer-autumn period in 1984. This shrimp is found to occur mainly in two areas, the first in the North Atlantic and the second in the South Hemisphere. In both regions the species occurs mainly in temperate and subtropical zones. The bathymetric distribution of A. pelagica lays between 200-2000 m depth, but mainly at 700-1800 m depth. The species migrates between the mesopelagic and bathypelagic areas. Spawning of the decapod shrimps occurs in August and the maximum population replenishment occurs in September. Larva hatch out at about 1000 m depth, then following some growth rise to 700-800 m depth. Initially females and males are represented by one-size groups. However, the females grow faster than males and later are often found at more then 1000 m depth. Thus, vertical ontogenetic migrations occur depending on size and age. Absolute individual fecundity (AIF - the quantity of ready to spawn oocytes in pre-spawning gonads) varies from 450 to 3600. It is estimated that with a one and a half times increase in body length, AIF increases by a factor of eight. Absolute realized fecundity (ARF - quantity of eggs present on a female's pleopods) varies from 560 to 3700. There were no statistically significant losses in eggs occurring from the pleopods during development.